MENGULAS POTENSI, EFEKTIFITAS DAN PROYEKSI RETRIBUSI PARIWISATA GILI TRAMENA PASCA COVID 19 - Muhammad Mujahid Dakwah; Ahmad Zaenal Wafik; Abdurrahman Abdurrahman; Himawan Sutanto (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
Recreational area fees and port service fees are an important source of PAD for the North Lombok District. It relies on the tourism sector as the main sector for regional revenue sources to carry out development acceleration so that it can get out of the only underdeveloped area in West Nusa Tenggara province. The study aims to analyze the potential and effectiveness and make projections of the fees for recreation areas and port services in Gili Tramena, North Lombok District. The findings showed that recreational area fees and port service fees from 2017 to 2021 tended to decrease and did not reach the target. It was due to the low process of extending and intensifying fees and external factors, namely the earthquake in 2018 and the COVID-19 pandemic in 2020. Based on calculations and data analysis, the total potential levy for recreational areas in 1 (one) year is IDR 7,607,653,250,00. With details of IDR 6,990,816,500.00 for foreign tourists and IDR 616,836,750.00 for domestic tourists. Meanwhile, the potential for the next 5 years is IDR 2,380,712,571.43 in 2022, IDR 2,576,320,095.24 in 2023, IDR 3,280,711,380.95 in 2024, IDR 3,985,102,666.67 in 2025, and IDR 4,689,493,952.38 in 2026. This potential can be reached, of course, with the political will of the local government to increasing PAD.